Analytical characterization of polyamide 11 used in the context of selective laser sintering: Physico-chemical correlations. (November 2020) - Scherer, Beate; Kottenstedde, Ingo Leonard; Bremser, Wolfgang; Matysik, Frank-Michael
Abstract: Polyamide 11 is an attractive material for additive manufacturing, however, in the selective laser sintering process it is subject to significant thermally induced stress. Suitable analytical methods are necessary to indicate any changes in the material properties. In this work, thermally stressed powder samples and printed tensile bars were analyzed by size exclusion chromatography-multi angle laser light scattering and differential scanning calorimetry. Based on the molecular weight distribution, crystallization and melting temperatures, ageing states of the investigated powders can be defined and transferred to the particles of the printed components. As a result, thermal stress led to an increase in molar mass and polydispersity. Moreover, calorimetric measurements indicated a delayed nucleation process as well as a decrease in polymorphism. Additionally, polymeric material with lower polydispersity values across the tensile bars could lead to decreasing elongation at break (εB ) values. For the crystallization onset temperature the opposite effect on εB was observed. Graphical abstract: Image 1 Highlights: Thermal ageing of polyamide 11 powders used for selective laser sintering. Average molecular weight greatly increases at high temperature storing. Influence of molecular weight on the elongation at break. Defining ageing states for powder particles of sintered parts. Mechanical behavior correlates with polydispersity and crystallization temperature.